The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1177/021849230501300103
|View full text |Cite
|
Sign up to set email alerts
|

Graft for Mycotic Thoracic Aortic Aneurysm: Omental Wrapping to Prevent Infection

Abstract: Nine cases of mycotic thoracic aortic aneurysm were treated surgically between July 1995 and March 2003. The aneurysms were located in the ascending aorta in 1 patient, the descending thoracic aorta in 5, and the thoracoabdominal aorta in 3. Preoperatively, 3 patients were in shock due to rupture of the aneurysm. All patients underwent aneurysmectomy and in-situ graft placement. In 5 patients, the graft was covered with a pedicled omental flap to prevent postoperative graft infection. There were 2 hospital dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…While extra-anatomical bypass was commonly performed in the past, anatomic reconstruction, resection of aneurysm wall, and covering of the prosthetic graft with omental wrapping have been introduced with favorable outcomes. 14,15) In our case, we selected in-situ prosthetic graft replacement because pus discharge was not observed during surgery. We considered omental wrapping; however, the omentum was severe atrophied from the inflammation, and we could not perform the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While extra-anatomical bypass was commonly performed in the past, anatomic reconstruction, resection of aneurysm wall, and covering of the prosthetic graft with omental wrapping have been introduced with favorable outcomes. 14,15) In our case, we selected in-situ prosthetic graft replacement because pus discharge was not observed during surgery. We considered omental wrapping; however, the omentum was severe atrophied from the inflammation, and we could not perform the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased risk of rupture and of postoperative graft infections. 3 In addition, aortic infection complicated by psoas abscess is associated with higher incidence of emergency operation, hospital mortality, prosthetic graft infection, and aneurysm-related mortality than infection without an accompanying psoas abscess. 4 There are few previously cases of aortic infection complicated by a psoas abscess and the incidence of psoas abscess in patients with a mycotic aortic aneurysm has been reported at 4-20%.…”
Section: Discussionmentioning
confidence: 99%
“…Kuniyoshi et al reported nine cases of infected thoracic or thoracoabdominal aneurysms, 3 and three of their patients died of infection-related reasons; two of the patients did not receive the omental fl ap transfer because of previous gastrectomy. Because rupture of the anastomotic site of graft replacement was the cause of their death, Kuniyoshi concluded that it was important to use the omental fl ap to prevent recurrence of infection.…”
Section: Discussionmentioning
confidence: 99%